Construcción de un arreglo de altavoces y su aplicación en audio personalizado (beamforming) - Ochoa Plaza, Daniel Hernando (Ingenierias, 2018)
The develop of personalized audio systems allows people to have private zone of listen withuot distubing the activity of people nearby. this kind of devices present a number of advantages compare to the headphones in daily situations in which people coexist in the same space, since they do not isolate people grom their environment and can cover large listening areas. For example where groups of people speak diferent languages and wish access to the audiovisual material. The present work consists of designing and implementing a speaker array textit beamforming, for the generation of 2 listening zones, in order to be implemented in personalized audio applications. A numerical analysis of the PMM method (Pressure Matching Method) was performed in MATLAB. The best configuration for reproducing spoken messages was determined. The regularization process necessary to make the implementation of the solution feasible when solving a inverse problem was analyzed. The array was constructed and the sound field was validated. In the work we present the description of the design and implmenetation of the speaker array beamforming designed for 2 listening zones with the method PMM